STRATEGI MARKETING POLITIK ANIES-SANDI DALAM MEMENANGKAN PILKADA DKI JAKARTA TAHUN 2017: BENARKAH MENGGUNAKAN POPULISME DAN POLITIK IDENTITAS? - Iswaranagari, Shania; -, Fitriyah - (Journal of Politic and Government Studies, 2021)
The Gubernatorial Election in Jakarta has its own distinction that the election often to be identified as a mini presidential election. Therefore, the election of 2017 gubernatorial in Jakarta draws attention to Indonesian people especially with the presence of the issue of SARA. The victory of Anies-Sandi in the 2017 election comes a contention, is the issue of SARA became part of the strategy for the victory of Anies-Sandi in the 2017 election? This study consists of researching the political marketing strategy Anies-Sandi, whether populism and identity politics are included in the strategy, and the group responses of the voters in DKI Jakarta. This study using a qualitative method with analytic descriptive solving by interviewing deeply to the relevant interviewees and using data from the survey institute. Data analysis processed with marketing politic, populism, and identity politic theories. The result of the study shows the victory of Anies-Sandi in the 2017 Jakarta Gubernatorial Election was inseparable from the advantage of the momentum of the Al-Maidah case from Ahok's side. But we must not close our eyes that the existence of a good, optimal, and appropriate marketing strategy carried out by Anies-Sandi also contributed to Anies-Sandi's victory in the 2017 Jakarta Gubernatorial Election. Political marketing strategy by presenting leader as a products who have a good and positive image makes the products offered accepted by the voters in DKI Jakarta. Diligent and well-structured digital and non-digital promotions are also able to boost Anies-Sandi's popularity in the eyes of voters. The process of place, community mapping and mature segmentation targeting sociological and psychological groups are good steps in predicting the votes that will be obtained. The results of the prices marketing process or psychological prices, show the good image received by Anies-Sandi is proven by the victory of Anies-Sandi's candidate in the The Gubernatorial Election in Jakarta. The results of this study also show that identity politics has indeed colored the 2017 Gubernatorial Election in Jakarta. However, the accusation that Anies-Sandi formed the identity politics of DKI Jakarta is not proven. Meanwhile, the populist strategy by getting closer to the Muslim community, clerics, and the use of religious and political narratives has in fact become part of the strategy carried out by Anies-Sandi. Sentiment and psychological emotions regarding Ahok's blasphemy case certainly influenced their choice. This shows the majority behavior voters in DKI Jakarta are sociological voters.